2005
DOI: 10.1111/j.1467-8608.2005.00385.x
|View full text |Cite
|
Sign up to set email alerts
|

Realism or idealism? Corporate social responsibility and the employee stakeholder in the global fast-food industry

Abstract: Bradford Scholars -how to deposit your paper Overview Copyright check• Check if your publisher allows submission to a repository.• Use the Sherpa RoMEO database if you are not sure about your publisher's position or email openaccess@bradford.ac.uk.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
53
0
1

Year Published

2006
2006
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(56 citation statements)
references
References 21 publications
2
53
0
1
Order By: Relevance
“…For example, Esbenshade (2001) argues that adopting codes of conduct provides a way for corporations both to prevent the enforcement of existing labour laws and forestall future legal reforms. Similar claims are readily found in previous research (e.g., Diller, 1999;Bondy et al, 2004;Royle, 2005;Arya and Salk, 2006), and, as Bartley (2005, p. 212) points out, a common argument is that " one unfortunate effect of the rise of private regulation will be to displace or 'crowd out' public regulation and legal accountability" .…”
Section: Plausible Motives For Adopting International Framework Agreesupporting
confidence: 63%
See 1 more Smart Citation
“…For example, Esbenshade (2001) argues that adopting codes of conduct provides a way for corporations both to prevent the enforcement of existing labour laws and forestall future legal reforms. Similar claims are readily found in previous research (e.g., Diller, 1999;Bondy et al, 2004;Royle, 2005;Arya and Salk, 2006), and, as Bartley (2005, p. 212) points out, a common argument is that " one unfortunate effect of the rise of private regulation will be to displace or 'crowd out' public regulation and legal accountability" .…”
Section: Plausible Motives For Adopting International Framework Agreesupporting
confidence: 63%
“…In recent years, many researchers have noted the existence of IFAs, their potential impact on workers' rights, and the high priority that signing these agreements has for global union federations (e.g., Gallin, 2000;Muller-Camen et al, 2001;Wills, 2001;Connor, 2004;Spooner, 2004;Chang and Wong, 2005;Royle, 2005;Andersen, 2006;Turnbull, 2006;Waddington, 2006;Doellgast and Greer, 2007). Connor (2004, p. 64), for example, notes that global union federations (GUFs) have "sought to persuade a number of companies to sign international framework agreements", but that "only a relatively small number of companies have been willing to participate in such programmes".…”
Section: Previous Research Into International Framework Agreementsmentioning
confidence: 99%
“…Royle's (2005) case study found a positive correlation between CSR and performance-oriented payment systems, and Vitaliano and Stella (2006) identified a positive relationship between CSR involvement and efficiency-based work practices. The positive association between CSR and labor flexibility was manifested in several qualitative studies (Benson 2008;Bonvin 2007;Smith and Helfgott 2010).…”
Section: Discussionmentioning
confidence: 99%
“…The organization's scale can have impact on local, national and global communities, by working with hundreds of suppliers, employing thousands of staff and serving millions of customers. Pressure to develop sustainable business practices comes from a variety of sources, including, regulating bodies encompassing local authorities, national Governments and the European Union; collective agreements; works councils; consumer pressure; values and cultural beliefs; and competitiveness achieved from new environmental initiatives (Nidumoul, Prahalad, & Rangaswami, 2009;Royle, 2005). The authors adopted an interview-based multi-case study approach (Eisenhardt, 1989;Eisenhardt & Graebner, 2007).…”
Section: Research Context and Methodsmentioning
confidence: 99%